Correction to: On the reproducibility of expert-operated and robotic ultrasound acquisitions (International Journal of Computer Assisted Radiology and Surgery, (2017), 12, 6, (1003-1011), 10.1007/s11548-017-1561-1) - Kojcev, Risto; Khakzar, Ashkan; Fuerst, Bernhard; Zettinig, Oliver; Fakhry, Carole; Dejong, Robert; Richmon, Jeremy; Taylor, Russell; Sinibaldi, Edoardo; Navab, Nassir (International Journal of Computer Assisted Radiology and Surgery, 2019)
The original version of this article unfortunately contained a mistake.
CRIS-Team Scopus Importer:2023-03-08